Desenvolvimento e caracterização de membranas de quitosana e casca de banana verde para cicatrização de feridas cutâneas - Franco, Patrícia Battaglini (2014)
Popularly known for its healing ability, the banana peel of the unripe fruit has been the object of this study forming a membrane to be used in skin injuries, together with chitosan, material widely studied as a biomaterial due to its healing properties, anti - inflammatory and antibacterial activity. The treatment of skin wounds (burns, ulcers, surgical wounds and diabetes) is a worldwide problem because of the possible complications of the healing process, such as infection, sepsis and even death. This study is interesting because banana is widely cultivated around the world, as well as the fact that chitosan is derived from chitin, a byproduct of the fishing industry, which makes its production economically and environmentally viable. For the preparation of the membranes based on chitosan , two different methods of extraction of the actives principles from the unripe bananas peels were studied, the method of drying and the method of decoction. Both methods has given good results in relation to the mechanical characteristics of the formed membranes, except the dried product that need to have reduced the quantity of power in order to produce a membrane with a better consistency. In the wound healing process the affected area should be kept moist. The behavior of the membranes in pH similar to blood and at temperature near to body temperature was done measuring the percentage of swelling capacity. All the membranes showed swelling capacity and permeability to water vapor. The analysis of contact angle showed the hydrofhilic nature of the membranes. The melting temperature, Tm, obtained by DSC analysis suggests that the membranes formed with the powder of the peels have a lower degree of crystallinity than the others. Both methods were efficient to prepare membranes that were able to inhibit the bacterial growth, S. aureus e E. coli. The conclusion is that the two methods studied for the extraction of metabolites of green banana peel were efficient for the formation of membranes capable to be used in wound healing characteristics.